Clients’ Perception of the Reliability of Property Investment Valuation in Nigeria - Ayedun, C.A.; Oloyede, S.A.; Iroham, O.C.; Oluwunmi, A.O. (Richtmann Publishing, 2011)
The question of overvaluation and under valuation has been a subject of intense debate in the valuation industry for more thantwo decades now. However, the discussion started taking prominent position in Nigeria in the late 1990s. The effect of unreliablevaluation in any economy cannot just be over emphasised as valuation estimates given by valuer during valuation exercises are verygermane to the decision to be taking by clients seeking for the valuer’s advice. This paper set out to ascertain the perception of clients to thereliability of valuation figures emanating from Nigerian valuers. Twenty four commercial banks and fifty property companies wererandomly chosen sampled in Lagos State. The data collected were analysed using descriptive statistic. The study revealed that clients wereof the opinion that valuation figures from Nigerian valuers were inaccurate and unreliable based on their experiences. The study concludedthat Nigerians valuers needed to be more thorough and painstaking in their valuation assignments so as to make valuation estimatesemanating from them more accurate and reliable.